Information theoretic aspects of the reliability of binary switching networks. - Farkas, John. (University of Ottawa (Canada), 1966)
The subject of this thesis is the analysis of binary switching networks. Many schemes for improving the performance of an unreliable binary switching element (gate) have been advanced. Only those relying on the combination of many unreliable gates into a more reliable network---performing the original function---are here considered. Some of the well-known schemes are analysed and reduced to a common format. This particular format was selected because it facilitated the application of information theoretic concepts to reliability improvement. Information theoretic concepts, applied under certain restrictions, resulted in the development of a lower bound, LB, on the unreliability (probability of error) of binary switching networks.
Keywords: Engineering, Electronics and Electrical.